Risky Financial Collateral, Firm Heterogeneity, and the Impact of Eligibility Requirements - Matthias Kaldorf; Florian Wicknig (ZBW - Leibniz Information Centre for Economics, 2021)
We study the eligibility of corporate bonds as collateral for central bank operations and its effect on interbank and corporate bond markets. While money market functionality increases in the amount of eligible assets, a thorough assessment of collateral policies must also account for endogenous responses of the corporate sector: banks increase demand for corporate bonds if they are eligible as collateral, and firms increase their leverage and default risk in response. This has adverse effects on the money market due to costs associated with deteriorating collateral quality. To jointly analyze the dynamics of collateral supply and collateral quality, we construct a heterogeneous firm model with defaultable bonds which banks use to collateralize money market borrowing. In this setting, eligible firms pay lower spreads and have higher leverage, consistent with empirical evidence. The central bank faces a trade-off between fostering collateral supply and increased risk-taking on the corporate bond market, which deteriorates collateral quality in equilibrium. Calibrating the model to Euro Area data, we find that reducing eligibility requirements from A- to BBB- increases collateral supply by 33%, while collateral default risk increases by 53%. Under an adverse shock to firm fundamentals, these numbers increase to 32% and 63%, i.e. collateral quality deteriorates disproportionately. Ultimately, firm fundamentals place restrictions on the efficacy of central bank collateral policy.
Keywords: E23; E44; G11; G32; 330; Money Markets; Financial Collateral; Eligibility Premia; Firm Heterogeneity; CreditRisk; Corporate Capital Structure